The pivotal role of primary care in meeting the health needs of people recently released from prison - Kinner, S.; Young, Jesse; Carroll, M. (2015)
OBJECTIVE: Australia's prison population is growing at a rate well in excess of population growth. Indigenous Australians are over-represented by a factor of 13. Prisoners are a profoundly marginalised group characterised by complex health and social needs. Despite improvements in health during incarceration, poor health outcomes after release are common, and the net effect of incarceration is usually health depleting. Given the need for effective care coordination, primary care plays a pivotal role in meeting the health needs of this population. In this paper we review what is known about patterns of primary care utilisation in ex-prisoners, identify evidence-based strategies for increasing access to primary care in ex-prisoners, and consider how such contact may shape subsequent health service outcomes. CONCLUSIONS: Primary care is a necessary but not sufficient condition for effective post-release support. Positive outcomes may depend more on the quality than the quantity of care received. Given massive over-representation of Indigenous people in Australia's prisons, and compelling evidence of preventable morbidity and mortality after release from prison, effective models of care for this population are an important component of closing the gap in Indigenous life expectancy.